1986
DOI: 10.1901/jeab.1986.46-199
|View full text |Cite
|
Sign up to set email alerts
|

Deprivation and Satiation: The Interrelations Between Food and Wheel Running

Abstract: Two experiments were designed to assess whether depriving rats of food would increase the reinforcement effectiveness of wheel running (Experiment 1) and whether satiation for wheel running would decrease the reinforcement effectiveness of food (Experiment 2). In Experiment 1, a progressive-ratio schedule was used to measure the reinforcement effectiveness of wheel running when rats were deprived or not deprived of food. Completion of a fixed number of lever presses released a brake on a running wheel for 60 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
1
3

Year Published

1988
1988
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 33 publications
3
66
1
3
Order By: Relevance
“…In a subsequent study (Lett et al 2001), this same group showed that naloxone attenuated the conditioned place preference induced by wheel running, implying that the rewarding effect of wheel running is mediated by endogenous opioids. Pierce et al (1986) have reported that rats will bar press vigorously to gain even brief access to running wheels.…”
Section: Discussionmentioning
confidence: 99%
“…In a subsequent study (Lett et al 2001), this same group showed that naloxone attenuated the conditioned place preference induced by wheel running, implying that the rewarding effect of wheel running is mediated by endogenous opioids. Pierce et al (1986) have reported that rats will bar press vigorously to gain even brief access to running wheels.…”
Section: Discussionmentioning
confidence: 99%
“…This inhibitory effect of exercise on food intake is shown by the transient decrease in food intake when groups of rats fed ad lib are introduced to the wheels (Altemus et al, 1996). Furthermore, Pierce, Epling,and Boer (1986) showed that both spontaneous and forced activity can decrease the reinforcing effectiveness of food, as if "exercise appears to substitute for eating" (Epling & Pierce, 1991, p. 144). The brain mechanism underlying this anorexic effect of exercise seems to involve the hypothalamic-pituitary axis (Rivest & Richard, 1990).…”
Section: At As a Protective Factor Against Activity-based Anorexiamentioning
confidence: 99%
“…Evidence for this is that rats will perform an operant response to gain a brief period of wheel running (e.g. Belke & Heyman, 1994;Iversen, 1993;Pierce et al, 1986;Premack, 1962). For example, rats will bar press vigorously on a fixed-ratio schedule for an opportunity to wheel run for 60 sec (Pierce et al, 1986).…”
Section: Introductionmentioning
confidence: 99%